2016
DOI: 10.1021/acs.jafc.6b03748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leaf Removal and Applied Water on Flavonoid Accumulation in Grapevine (Vitis vinifera L. cv. Merlot) Berry in a Hot Climate

Abstract: The relationships between variations in grapevine (Vitis vinifera L. cv. Merlot) fruit zone light exposure and water deficits and the resulting berry flavonoid composition were investigated in a hot climate. The experimental design involved application of mechanical leaf removal (control, pre-bloom, post-fruit set) and differing water deficits (sustained deficit irrigation and regulated deficit irrigation). Flavonol and anthocyanin concentrations were measured by C18 reversed-phased HPLC and increased with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 64 publications
7
49
1
1
Order By: Relevance
“…In small plot trials water stress was effective in altering plant canopy development, and leaf area was directly related to canopy microclimate (Intrigliolo and Castel, 2010;Keller et al, 2016;Kraus et al, 2018). Previous studies had also shown that canopy microclimate had a determining role in altering berry chemistry biosynthesis (Cook et al, 2015;Yu et al, 2016). In our current work, we did not observe differences in leaf area even though the plant water status was consistently separated throughout the two seasons.…”
Section: Yield Componentssupporting
confidence: 48%
“…In small plot trials water stress was effective in altering plant canopy development, and leaf area was directly related to canopy microclimate (Intrigliolo and Castel, 2010;Keller et al, 2016;Kraus et al, 2018). Previous studies had also shown that canopy microclimate had a determining role in altering berry chemistry biosynthesis (Cook et al, 2015;Yu et al, 2016). In our current work, we did not observe differences in leaf area even though the plant water status was consistently separated throughout the two seasons.…”
Section: Yield Componentssupporting
confidence: 48%
“…They achieve this by absorbing highly energetic solar wavelengths, thereby limiting the generation of ROS due to photooxidation. Although flavonol levels have been found to be negligibly low in developing grape berries, the transcription and subsequent accumulation of these compounds in both a light-dependent and development-independent manner have been reported and extensively characterized in grapes (reviewed by Downey et al, 2006; Czemmel et al, 2009; Matus et al, 2009; Malacarne et al, 2016; Yu et al, 2016; Pastore et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cultivar, the objectives range from improving the acid balance (Hunter and Visser, 1990; Toda et al, 2013; Baiano et al, 2015); improving anthocyanin/color stability (Chorti et al, 2010; Sternad Lemut et al, 2011; Lee and Skinkis, 2013; Baiano et al, 2015; Song et al, 2015; Guan et al, 2016; Yu et al, 2016; Pastore et al, 2017); increasing specific secondary metabolites such as volatile aroma precursors (Staff et al, 1997; Tardaguila et al, 2010; Feng et al, 2015; Song et al, 2015; Suklje et al, 2016; Young et al, 2016) or lowering of metabolites that are perceived negatively in the grapes/wines (Sala et al, 2004; reviewed in Sidhu et al, 2015). One of the main outcomes of leaf removal in the bunch zones is the accumulation of protective phenolic compounds i.e., anthocyanins (Lee and Skinkis, 2013; Guan et al, 2016; Lee, 2017) and flavonols (Yu et al, 2016; Pastore et al, 2017), as well as changes to volatile aroma compounds i.e., the norisoprenoid, β-damascenone (Feng et al, 2015; Young et al, 2016) and monoterpenes (Song et al, 2015; Young et al, 2016). These studies have all highlighted the adaptability of the grapevine berries to the changed microclimate and have also provided scope to investigate mechanisms of perceiving and adapting to the stresses linked to changes in microclimate.…”
Section: Introductionmentioning
confidence: 99%
“…BERRY FLAVONOID COMPOSITION. Flavonoid composition of the berry was determined on a separate set of 20-berry samples following the procedure as developed by Cook et al (2015) and Yu et al (2016) using reversed-phase high-performance liquid chromatography (HPLC). At harvest, 20-berry samples were collected, weighed, and stored at -80°C until analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…An additional two, eightnode canes are also attached onto a catch wire 66 inches above the vineyard floor. Although this traditional training system facilitated production goals, such as mechanical harvesting, it was proven difficult to facilitate mechanical management, such as dormant pruning (Kurtural et al, 2012) and shoot removal (Terry and Kurtural, 2011), with some success in mechanical leaf removal (Cook et al, 2015;Yu et al, 2016). Previously, we investigated mechanizing dormant and growing season cultural practices on grapevine trained to common trellis systems used in California (Brillante et al, 2018;Kurtural et al, 2012Kurtural et al, , 2013Terry and Kurtural, 2011;Wessner and Kurtural, 2013) in vineyards trellised specifically for experimental purposes.…”
mentioning
confidence: 99%